2003
DOI: 10.1037/0278-6133.22.5.471
|View full text |Cite
|
Sign up to set email alerts
|

Observer ratings of health and sickness: Can other people tell us anything about our health that we don't already know?

Abstract: After administering interviews covering health conditions, physical limitations, optimism, and affect to 851 older adults, interviewers rated the health and sickness of the interviewees. Observers' ratings of health and sickness were more highly correlated with the severity of participants' self-reported health conditions than were participants' self-ratings of health. This finding is likely attributable to participants' self-ratings of health being more highly correlated with their optimism and positive affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 42 publications
3
31
0
1
Order By: Relevance
“…Although this literature is relatively new and, therefore, limited, several studies have demonstrated that self-ratings of health may be subject to optimism and positive effect [26,27]. In one study, the observer ratings of subjects' health and sickness exhibited a stronger association with all-cause mortality than self-ratings of health [26].…”
Section: Discussionmentioning
confidence: 97%
“…Although this literature is relatively new and, therefore, limited, several studies have demonstrated that self-ratings of health may be subject to optimism and positive effect [26,27]. In one study, the observer ratings of subjects' health and sickness exhibited a stronger association with all-cause mortality than self-ratings of health [26].…”
Section: Discussionmentioning
confidence: 97%
“…This is not a surprise. Compared to SRH, evaluation by interviewer could be less affected by subjective factors (Todd and Goldman, 2013) and thus may have some advantages over SRH (Brissette, Leventhal, and Leventhal, 2003). Because interviewers usually rate respondents' health at the end of the interview, which is the practice in the CLHLS, interviewers can incorporate information on a respondent's reported health and health-related conditions and information from their own observations while communicating with respondents.…”
Section: Discussionmentioning
confidence: 99%
“…This is because interviewers may incorporate respondents' reported health information into evaluation when such an assessment is performed at the end of interview (Feng, Zhu, Zhen et al, 2016), and because interviewers' assessments are also susceptible to subjectivity (Brissette, Leventhal, and Leventhal, 2003;Feng, Zhu, Zhen et al, 2016). Some research has indeed shown that factors such as respondents' socioeconomic status affect not only SRH, but also affect physicians' and interviewers' reporting of health outcomes (Smith and Goldman, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considerable research attention has been directed toward understanding the information people incorporate into their self-ratings of health (e.g., [4,5]). Following this research strand, a plausible explanation of the expected prediction of lipids by SRH is that people, when asked for a global evaluation of their health, take into consideration their own health behaviors, including dietary behavior that could lead to subsequent lipid elevations [47].…”
Section: Introductionmentioning
confidence: 99%